FRI0050 Type ii collagen secreted from articular chondrocytes is mainly destroyed by cathepsin s in ra mice. (15th June 2017) - Zhao, J; Huang, Q; Ren, H; Yang, M
Abstract : Background: Mast cells have long been recognized to increase strikingly in number in the synovial membrane of rheumatoid arthritis (RA), accounting for 5% of the surface synovial membrane cells. Type II collagen has the longest half-life in cartilage matrix. The main cells which might affect articular cartilage in RA are synovial fibroblasts, synovial macrophages and mast cells. The latter two could express cathepsin S. Objectives: We aimed to find the cells which have the biggest influence on type II collagen secreted from articular chondrocytes and the possible mechanisms in RA mice. Methods: Four types of cells from collagen-induced arthritis model-established C57BL/6 mice were primary cultured, including synovial fibroblasts, peritoneal macrophages, bone marrow-derived mast cells and articular chondrocytes. The first three were co-cultured with articular chondrocytes separately. LHVS, a specific inhibitor of cathepsin S, and E64, a broad-spectrum inhibitor of cysteine protease, were added into the cocultures of macrophages and articular chondrocytes separately. Also, C48/80, an activator of mast cells, LHVS, and E64 were added into the cocultures of mast cells and articular chondrocytes separately. The culture supernatant fluid was collected. The concentration of cathepsin S and type II collagen were measured by ELISA. The expression of type II collagen mRNA in each group was detected with RTPCR. Results: Macrophages and mast cells expressed cathepsin S, while synovial fibroblasts did not express cathepsin S. Synovial fibroblasts had little effect on the expression of type II collagen from articular chondrocytes. When articular chondrocytes were co-cultured with macrophages, the expression of type II collagen decreased (8.79±2.79ng/ml), compared with the control group (17.75±7.84ng/ml). The secretion of type II collagen could return to normal by the inhibitors of cathepsin S, both LHVS (16.15±8.05 ng/ml) and E64 (12.55±6.64 ng/ml). When articular chondrocytes were co-cultured with mast cells, the type II collagen could be restrained by C48/80 (9.82±0.42ng/ml), compared with the control group (26.09±9.34ng/ml). Similarly, the secretion of type II collagen could return to normal by LHVS and E64 (16.15±8.05 ng/ml, 12.55±6.64 ng/ml, respectively). There was no significant difference in the expression of type II collagen mRNA between different groups. It showed that the type II collagen was not suppressed at the transcription level, but was mainly destroyed by cathepsin S after secretion. Conclusions: Macrophages and mast cells are the major sources of cathepsin S, which might be the main factor that destroys type II collagen secreted from articular chondrocytes in RA mice. Disclosure of Interest: None declared